2010
DOI: 10.1038/emboj.2010.240
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal organization of the E. coli PTS components

Abstract: The phosphotransferase system (PTS) controls preferential use of sugars in bacteria. It comprises of two general proteins, enzyme I (EI) and HPr, and various sugar-specific permeases. Using fluorescence microscopy, we show here that EI and HPr localize near the Escherichia coli cell poles. Polar localization of each protein occurs independently, but HPr is released from the poles in an EI- and sugar-dependent manner. Conversely, the β-glucoside-specific permease, BglF, localizes to the cell membrane. EI, HPr a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
73
0
7

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(83 citation statements)
references
References 42 publications
3
73
0
7
Order By: Relevance
“…Notably, when bglG is transcribed without bglF, its transcripts localize to the poles, 25 where the BglG protein forms a complex with the general PTS proteins after it is released from the membrane pre-complex upon sugar stimulation. 12 To the best of my knowledge, this is the first demonstration of changes in mRNA localization depending on changes in the site of complex formation in response to environmental stimuli in any organism. Summarily, our study establishes for the first time the existence of translationindependent mechanisms for targeting bacterial mRNAs to the subcellular regions where their protein products are subsequently detected.…”
Section: Localization Of Bacterial Proteins Via Mrna Targetingmentioning
confidence: 99%
See 4 more Smart Citations
“…Notably, when bglG is transcribed without bglF, its transcripts localize to the poles, 25 where the BglG protein forms a complex with the general PTS proteins after it is released from the membrane pre-complex upon sugar stimulation. 12 To the best of my knowledge, this is the first demonstration of changes in mRNA localization depending on changes in the site of complex formation in response to environmental stimuli in any organism. Summarily, our study establishes for the first time the existence of translationindependent mechanisms for targeting bacterial mRNAs to the subcellular regions where their protein products are subsequently detected.…”
Section: Localization Of Bacterial Proteins Via Mrna Targetingmentioning
confidence: 99%
“…11 Why has the cell evolved a polarly localized complex to control organelles that are scattered around the cell periphery? In a study that we recently published in the EMBO Journal, 12 we showed that the control center of the PTS system, which consists of the general PTS proteins, EI and HPr, also localizes to the cell poles. The different proteins that are regulated by this polar center via HPrmediated phosphorylation localize around the cell circumference (sugar permeases) or in the cytoplasm (e.g., IIA glc ).…”
Section: Spatial Organization Of Bacterial Signaling Systemsmentioning
confidence: 99%
See 3 more Smart Citations